A Case of Dibothriocephalosis (Dibothriocephalus latus) from Iseo Lake (Northern Italy): An Update on a Persistent Sanitary Issue - Vasco Menconi; Lisa Guardone; Elena Lazzaro; Romina Bottazzo; Valeria Besutti; Patrizia Danesi; Amedeo Manfrin; Andrea Basso; Giuseppe Arcangeli; Luana Cortinovis; Ewa Bilska-Zając; Giorgia Angeloni (Pathogens)
Dibothriocephalosis is a fish-borne parasitic zoonosis that is caused by tapeworms of the Dibothriocephalus (syn. Diphyllobothrium) genus. This paper describes a human case of dibothriocephalosis associated with the consumption of a presumably infected fish, prepared at a restaurant near Iseo Lake (northern Italy). A month after, the patient found a segment of a worm in her stool. Molecular analysis identified it as Dibothriocephalus latus (syn. Diphyllobothrium latum). Several studies reported D. latus infections in patients from the subalpine regions of Switzerland, France, and Italy, but no cases have been reported from this area in the last 10 years. This report updates the epidemiology of dibothriocephalosis and emphasises the importance of collaboration among healthcare institutions for a prompt diagnosis and the need for food safety education for Food Business Operators and consumers to reduce transmission risks.